(untitled) (Sociologisk Forskning, 2025)
Research on class mobility is a well-established field with a long tradition within sociology. Several qualitative studies have explored the experiences of class mobility, both focusing on class and from an intersectional perspective. However, these studies have almost exclusively dealt with the individual aspects of upward class mobility. This article, by contrast, explores the collective aspects, specifically the significance of actual and imagined communities in class mobility narratives. Drawing on interviews and theories on identification, community, and place, this study analyzes the mobility experiences of class-mobile individuals from the racialized working class who grew up in förorten (marginalized neighborhoods) in Sweden. The article identifies two central communities in the narratives. The first is the actual family as community, where class mobility is portrayed as a collective goal, shaped by the family’s sacrifices and shared aspirations. The second community is an imagined place-based community connected to förorten as a symbolic space. Referring to these place-bound identifications, the participants strive both to ”give back” to these communities and to act as good representatives of förorten.